(untitled) (Bangladesh Pharmaceutical Journal, 2012)
The present study was designed to evaluate the analgesic and anti-inflammatory activities of the ethanol extract of whole plant of Asteracantha longifolia Nees (family Acanthaceae) in mice. The analgesic activity was determined for its central and peripheral pharmacological actions using hotplate, formalin induced pain and acetic acid-induced writhing test in mice. Anti inflammatory effects were determined by ear swelling induced by croton oil, xyleneinduced ear edema, leukocyte migration induced by carrageenan, cotton pellet-induced granuloma formation. Tramadol (10 mg/kg) and Ibuprofen (100 mg/kg) were used as reference analgesic agents. The crude ethanol extract showed a significant inhibition of ear swelling caused by croton oil and xylene in mice. The crude extract decreased leukocyte migration induced by carrageenan, also moderately inhibited the weight of granuloma induced by a cotton pellet, as well as the formalin-induced pain. The extract given by p.o. route, produced significant inhibition of abdominal constrictions caused by acetic acid. Moreover, the extract also showed moderate analgesic activity on the hot plate pain threshold in mice. These data demonstrated that the plant may contain bioactive compounds possessing anti-inflammatory and analgesic activities. DOI: http://dx.doi.org/10.3329/bpj.v15i2.12586 Bangladesh Pharmaceutical Journal 15(2): 171-176, 2012